Adélie penguins north and east of the ‘Adélie gap’ continue to thrive in the face of dramatic declines elsewhere in the Antarctic Peninsula region - Michael Wethington; Clare Flynn; Alex Borowicz; Heather J. Lynch (Scientific Reports, 2023)
Abstract While population declines among Adélie penguins and population increases among gentoo penguins on the Western Antarctic Peninsula are well established, the logistical challenges of operating in the sea ice-heavy northern tip of the Antarctic Peninsula have prohibited reliable monitoring of seabirds in this region. Here we describe the findings of an expedition to the northern and eastern sides of the Antarctic Peninsula—a region at the nexus of two proposed Marine Protected Areas—to investigate the distribution and abundance of penguins in this region. We discovered several previously undocumented penguin colonies, completed direct surveys of three colonies initially discovered in satellite imagery, and re-surveyed several colonies last surveyed more than a decade ago. Whereas our expectation had been that the Peninsula itself would divide the areas undergoing ecological transition and the apparently more stable Weddell Sea region, our findings suggest that the actual transition zone lies in the so-called "Adélie gap," a 400-km stretch of coastline in which Adélies are notably absent. Our findings suggest that the region north and east of this gap represents a distinct ecoregion whose dynamics stand in sharp contrast to surrounding areas and is likely to be impacted by future conservation measures.